Green finance, green technology innovation, and carbon emission reduction - Xing Xiong; Wenhong He; Sirong Chen; Yuhang Wu (Environmental Research Communications)
Green finance, as a financial innovation tool that integrates finance and environmental protection, has become a crucial means of achieving carbon emission reduction. Based on panel data from 334 prefecture-level cities in China from 2000 to 2021, a two-way fixed effects model was constructed to empirically analyze the impact and mechanism of green finance on carbon emission reduction. The main findings are as follows: First, green finance significantly reduces carbon emission intensity; second, green technology innovation plays a mediating role in the impact of green finance on carbon emission intensity; third, green finance has the strongest effect in reducing direct greenhouse gas emissions; fourth, green investment and green bonds have the most substantial effect on reducing carbon emissions, while the direct effect of green equity on reducing carbon emission intensity is not significant. Therefore, to enhance the level of green finance, it is necessary to accelerate the development of green finance and actively build a synergistic development system between green finance and related technological innovations.